Design of Mail Delivery Automation for Student's Thesis Invitation - Mapaly, Heilbert Armando (Jurnal Teknik Informatika, 2021)
Abstract — Higher education plays an important role in producing competitive human resources. The final project is an academic paper of study results and / or research results, which is carried out independently by students through proposal seminars and result seminars under the guidance of a student supervisor team. In its implementation, it is necessary to distribute the Session schedule to the examiners to attend the Session. This research will try to be able to take advantage of automation on the system to be able to distribute the Assignment Session invitations so that it can help the Study Program in the process. This research succeeded in creating an automation system using the CodeIgniter framework. When the schedule has been determined, the system will automatically send an to the Session Examining Team regarding the Session Schedule.